2003
DOI: 10.1111/1467-8306.9303002
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Regional Storm Tracking and Teleconnections on Winter Precipitation in the Northeastern United States

Abstract: Secular changes in regional storm tracking are examined as physical mechanisms for observed teleconnections between the New England hydroclimate and four predictor variables: the Southern Oscillation Index, the North Atlantic Oscillation, the Pacific Decadal Oscillation, and regional sea-surface temperatures. The main modes of New England winter precipitation, snowfall, and cyclone variability are resolved using varimax rotated principal component analysis. The first rotated principal component of regional cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 47 publications
2
56
0
Order By: Relevance
“…The Great Lakes region receives snowfall based on the lake effect, a phenomena caused by cold arctic air blowing over the relatively warm lakes, picking up moisture, then rising, causing the moisture to condense, and finally snowing over the downwind land (Heidorn, 1998;Niziol et al, 1995). Numerous studies have investigated wintertime precipitation in the northeast (Bradbury et al, 2002(Bradbury et al, , 2003Hartley, 1996;Hartley and Keables, 1998) as previously outlined, attributing variability to sea-surface temperatures, geopotential heights, and the NAO, allowing for colder temperatures, causing more precipitation to fall as snow. Contrastingly, TSF and NSD were very low (less than 5 days of snow and less than 200 mm of total season snowfall) south of Missouri, Kentucky, and Virginia, due to warmer seasonal temperatures.…”
Section: General Relationships Of Climate Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Great Lakes region receives snowfall based on the lake effect, a phenomena caused by cold arctic air blowing over the relatively warm lakes, picking up moisture, then rising, causing the moisture to condense, and finally snowing over the downwind land (Heidorn, 1998;Niziol et al, 1995). Numerous studies have investigated wintertime precipitation in the northeast (Bradbury et al, 2002(Bradbury et al, , 2003Hartley, 1996;Hartley and Keables, 1998) as previously outlined, attributing variability to sea-surface temperatures, geopotential heights, and the NAO, allowing for colder temperatures, causing more precipitation to fall as snow. Contrastingly, TSF and NSD were very low (less than 5 days of snow and less than 200 mm of total season snowfall) south of Missouri, Kentucky, and Virginia, due to warmer seasonal temperatures.…”
Section: General Relationships Of Climate Variablesmentioning
confidence: 99%
“…Additionally, they found that lower 700 mb geopotential heights over the southeastern U.S. and Atlantic in wintertime, when preceded by a cold fall, tend to result in lower wintertime temperatures, creating more potential for precipitation to fall as snow. Bradbury et al (2003) linked New England snowfall variability to the NAO, ENSO, and the pacific decadal oscillation (PDO) via regional storm tracking patterns. They also identify a significant correlation between snowfall and regional SST anomalies, and suggest snowfall may also The previous section illustrates how past research has contributed to the understanding of snowfall variability over the eastern U.S. More investigation into the specific patterns, circulations, and areas of the globe that influence snowfall variability is necessary to make accurate predictions of seasonal snowfall for water managers and policy makers in this region.…”
Section: Introductionmentioning
confidence: 99%
“…A more thorough understanding of regional hydroclimate variability and the associated linkages to known hemispheric/global patterns may assist in future predictive capabilities throughout North America. The patterns of atmospheric pressure centers described by these indices influence hydroclimatology by modulating midtropospheric circulation patterns and storm tracking (12). An important reconstruction of the position and amplitude of the vortex trough in the NE over the past millennium demonstrated that this dominant atmospheric feature has influenced precipitation variability over the late Holocene (13).…”
mentioning
confidence: 99%
“…This time period includes the El Niño event of late 1997/early 1998 and the 1999 La Niña event. However, the impacts of ENSO are minimal in New England (Ropelewski & Halpert 1987, Halpert & Ropelewski 1992, Bradbury et al 2003) and these occurrences should not affect the basic derivation of the synoptic classification. This use of daily maps should yield a reliable climatology, because the frequencies of synoptic-scale pressure patterns are largely unaffected by diurnal variability.…”
Section: Introductionmentioning
confidence: 99%